Compressive strength and behaviour of full and partial CFRP confined concrete columns / Muhammad Amir Shafiq Rahamad Ali... [et al.] - Rahamad Ali, Muhammad Amir Shafiq; Ahmad Zakwan, Fariz Aswan; Ahmad, Hazrina; Ismail, Ruqayyah; Ismail, Badrul Nizam (Universiti Teknologi MARA, Pulau Pinang, 2022)
Concrete columns encased in carbon fibre reinforced polymer (CFRP) have been extensively explored for usage in civil engineering constructions in recent years. However, the performance of these CFRP concrete systems is still questionable since CFRP application is relatively costly. The study focuses on the axial compressive loadings and strength of two different types of CFRP confinement configurations. Fifteen (15) cylindrical concrete column samples of 1 m height and 200 mm diameter were fabricated, including three (3) control samples (without CFRP) and twelve (12) CFRP cylindrical concrete columns. Two layers of CFRP confinement gave more additional support and strength to the column’s samples for both full and partial confinement. Full 2-layers confined columns obtained 65.53% and partial 2-layers confined columns obtained 48.35% higher than the unconfined samples (control samples) on average. The load-displacement and stress-strain results are also discussed in this paper. A full layer of CFRP gave higher compressive strength in this study but partial CFRP confinement gave enough strength to the column which was more than 35% higher compressive strength compared to the control samples on average. The knowledge in this research field can be used as the basis for future structural rehabilitation work.